(untitled) (Research, Society and Development, 2022)
Objective: To determine the rate of dental caries and periodontal rates in Mozambican population. Material and Methods: The sample size was 722, categorized in age groups of 6,12, 15-19 and 35-44 in public schools and markets randomly selected in five provinces of Mozambique (Maputo, Gaza, Manica, Tete and Zambezia), in urban and rural areas. Clinical examinations were performed by calibrated examiners using WHO, DMFT/dmft and CPI indexes. Data analysis was descriptive and analytical, using a Chi-square test and Pearson’s correlation (P <0.05). Results: The adults aged 35-44 presented higher dental caries (DMFT=1.94) than those aged 6 years (dmft = 1.16), 12 years (DMFT=0.60), and 15-19 years (DMFT=0.87). Dental caries was more prevalent in urban area (1.89) than rural area (1.33) with statistical difference p=0.004. The dental caries was the highest at Manica Province n=68 (85%) and lowest in Tete Province n=70 (31%). Regarding to periodontal status, the most prevalent disease, was Calculus in adults of 35-44 n=95 (59.4%), and the prevalence of individual free of periodontal disease was n=182 (34.3%). Conclusion: When assessing this population for dental caries and periodontal status, the 35-44 years old presented the highest rate of both diseases at all age.